STRATEGI PENGELOLAAN DUYUNG (Dugong dugon) DI PROVINSI KEPULAUAN BANGKA BELITUNG - Retfi Wiseli (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2017)
The cultivation of mermaids by Kurau fishermen of Central Bangka Regency Who netted his net as he sailed on the week of April 16, 2017 Based on information from http://bangka.tribunnews.com. The mermaid is alive with an estimated length of about 2 meters with a weight of 200kg. Dugongs brought fishermen to the home of one of the residents, Placed into a pool made of large plastic filled with sea water and topped with a tarpaulin. The mermaids are released back into their habitat after mediation and agreement between the fishermen. The mermaids are released back into their habitat after mediation and agreement between the fishermen And Mangkol Foundation Management Foundation in collaboration with activists Animal Lovers Bangka Island (Alobi) money replacement cost of 8 million Rupiah. The incidence of capturing mermaids is not just one time, but 4 times occur in the first six months in 2017. This study uses preference analysis by extracting information from fishermen, youth, fish collectors and fishermen wives by using questionnaires totaling 25 respondents And Potential Analysis of Potential Resources and Constraints Using SWOT. The existence of this study is expected to determine the okum tor mermaid management strategy as well as recommendations and information for decision makers in the framework of determining the conservation area of Bangka Belitung